2008
DOI: 10.1103/physrevc.78.061601
|View full text |Cite
|
Sign up to set email alerts
|

Difference between interaction cross sections and reaction cross sections

Abstract: We revisit the commonly accepted notion that the difference between interaction and reaction cross sections is negligible at relativistic energies, and show that, especially in small mass number region, it is large enough to help probe nuclear structure. For analyses of the difference, we construct "pseudo data" for the reaction cross sections using a phenomenological black-sphere model of nuclei since empirical data are very limited at high energies. The comparison with the empirical interaction cross section… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…However, this is not always the case even for high energy data, as suggested by using pseudodata for total reaction cross sections that can be obtained from the measured elastic diffraction peak angles for stable nuclei via the black sphere model [39]. Within the framework of the full Glauber scattering theory, Novikov and Shabelski [40] also confirmed that the differences are appreciable.…”
Section: Proton Elastic Scattering and Total Reaction Cross Sections mentioning
confidence: 56%
“…However, this is not always the case even for high energy data, as suggested by using pseudodata for total reaction cross sections that can be obtained from the measured elastic diffraction peak angles for stable nuclei via the black sphere model [39]. Within the framework of the full Glauber scattering theory, Novikov and Shabelski [40] also confirmed that the differences are appreciable.…”
Section: Proton Elastic Scattering and Total Reaction Cross Sections mentioning
confidence: 56%
“…2. These are compared with the experimental interaction cross sections [17], which are expected to be close to the reaction cross sections for neutron-rich nuclei [7,38,46]. For comparison, we also show the result of the previous analysis [14] at a similar one neutron separation energy, even though the single-potential is different from the one used in the present analysis.…”
Section: 3132 Ne Isotopesmentioning
confidence: 75%
“…Furthermore, this formula can be easily extended to nucleus-nucleus reactions [5,6] and is shown to reproduce the empirical data quite well for the energy above 100 MeV/nucleon [5,6].…”
Section: Introductionmentioning
confidence: 84%